Teaching Anxiety of Primary School English Teachers in Samut Prakan Province - Tujinda, Kwanluk (Huachiew Chalermprakiet Law Journal, 2025)
Abstract This research aimed to investigate the factors affecting the anxiety of primary school English teachers in Samut Prakan Province. The sample consisted of 80 teachers, including those who graduated with a major in English and those from other fields, teaching in small- and medium-sized schools. The sample was selected through purposive sampling. The research instrument was a questionnaire measuring teaching anxiety, with a reliability coefficient of 0.94. Data were analyzed using descriptive statistics, including percentage, mean, and standard deviation. The research findings revealed that the overall level of teaching anxiety among the teachers was moderate. The factor contributing most to the anxiety was personal factors in teaching (mean = 2.78, standard deviation = 1.17), followed by social and environmental factors (mean = 2.59, standard deviation = 1.31), and learning factors (mean = 2.56, standard deviation = 1.10), respectively. The expected benefits of this study include providing guidelines for enhancing the teaching capacity of primary school English teachers, reducing teaching anxiety, and fostering greater confidence in conducting English instruction effectively.